Pengaruh Persepsi, Teknologi, Kemudahan Penggunaan, dan Difusi Inovasi terhadap Minat Adopsi E-Money pada Generasi Z di Kota Denpasar - Fatmayoni, I Gusti Agung Ayu Intan; Paramarta, Pande Made Ari Ananta; Pradnyani, Ni Wayan Asri; Harthawan, I Gusti Ngurah Putra (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to analyze the influence of Perception, Technology, Ease of Use, and Diffusion of Innovation on E-Money Adoption Intention among Generation Z in Denpasar City. Generation Z grew up in an intensive digital ecosystem, thus having an adaptive character towards application-based financial innovations. The research approach uses a quantitative method with Structural Equation Modeling analysis based on Partial Least Squares (SEM-PLS). The research sample consisted of 150 respondents determined through probability sampling techniques with the simple random sampling method. The results show that all independent variables have a positive and significant effect on E-Money Adoption Intention. Ease of Use has the most dominant influence, followed by Perception, Technology, and Diffusion of Innovation. The R Square value of 0.682 indicates that the model is able to explain 68.2% of the variation in adoption interest. This finding confirms that psychological factors, the quality of the technology system, and social influence play an important role in encouraging the acceptance of digital payments. The implications of the study emphasize the importance of increasing digital financial literacy, strengthening security systems, and data protection regulations to support sustainable digital economic growth in Denpasar.